2016
DOI: 10.1136/bjophthalmol-2016-308400
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of intravitreal anti-VEGF therapy in eyes with both neovascular age-related macular degeneration and diabetic retinopathy

Abstract: Outcomes analysis of intravitreal anti-VEGF therapy for eyes with both neovascular AMD and DR showed stabilisation of BCVA and reduction of CMT, along with stable or improved DR stage throughout follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 31 publications
(17 reference statements)
0
4
0
Order By: Relevance
“…VEGF has long been known to contribute to angiogenesis and increase the permeability of the vascular endothelium. Anti-VEGF therapy aimed at preventing macular oedema and retinal neovascularisation has been widely used, and it has produced satisfactory results [4851]. EPO is still being considered a “two-faced Janus” factor in the retina where it acts by binding to a trans-membrane receptor (EPOR).…”
Section: Discussionmentioning
confidence: 99%
“…VEGF has long been known to contribute to angiogenesis and increase the permeability of the vascular endothelium. Anti-VEGF therapy aimed at preventing macular oedema and retinal neovascularisation has been widely used, and it has produced satisfactory results [4851]. EPO is still being considered a “two-faced Janus” factor in the retina where it acts by binding to a trans-membrane receptor (EPOR).…”
Section: Discussionmentioning
confidence: 99%
“…Although this route of administration is a common clinical practice in several diseases, like age-related macular degeneration (AMD) and diabetic retinopathy, 18 easier administration routes would be very important from the clinical point-of-view. Topical administration (eye drops) provides a suitable noninvasive method for treating ophthalmic diseases.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, although screening programs have been established and early diagnoses and treatments have been made for the disease, DR still remains the most common cause of visual impairment and blindness [23]. In recent studies, inhibitors of vascular endothelial growth factor (VEGF) have been found to revolutionize the management and treatment of DR and possess special efficacy on diabetic macular edema [24]. However, anti-VEGF agents are not effective in all patients, reinforcing and confirming the fact that DR is a multi-factorial disease which needs to be further elucidated [25].…”
Section: Discussionmentioning
confidence: 99%